Public Health Entrepreneurship: A Novel Path for Training Future Public Health Professionals - Becker, Elisabeth R. B.; Chahine, Teresa; Shegog, Ross (Frontiers in Public Health, 2019)
Background: As schools of public health adapt to the new Council on Public Health (CEPH) competencies there is increased relevance in training public health professionals in public health entrepreneurship. Public health entrepreneurship provides an alternate process to traditional academic approaches focusing on translating public health knowledge into effective, sustainable, and scalable solutions. Objective: This study reports student perceptions of public health entrepreneurship and training needs for successfully equipping future public health professionals. Methods: Focus groups were conducted in April 2018 with graduate public health students in pilot entrepreneurship courses at two U.S.-based CEPH-accredited schools of public health. Results: Participating students (n = 29) were mainly pursing MPH degrees (62%) within Health Management and Policy (38%) or Health Promotion/Global Health (31%) departments. Most students (52%) were between 21 and 30 years old. For 71% of students this was their first academic course with a focus on entrepreneurial thinking. Four themes emerged regarding public health entrepreneurship and training needs for becoming a successful public health professional of the future. Students confirmed a place for public health entrepreneurship in the emerging educational paradigm because it is action-oriented, skills-driven, and fosters innovation through inter-professional collaboration and cross-pollination of knowledge and skills between professional disciplines. Conclusions: The competencies required for public health entrepreneurship are in alignment with CEPH competencies and are well-received by the next generation of public health professionals as an adjunct but nascent approach to stimulate public health innovation.